Pengaruh Minat Berwirausaha, Skill Training dan Open Innovation Oleh Balai Latihan Kerja dalam Mendukung Keberlanjutan UMKM di Kota Magelang - Bagas Gumintang; Filda Khoirun Nikmah; Purwati Purwati (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This research was conducted as decision-making by the Magelang City Vocational Training Center regarding the sustainability of MSMEs, especially in Magelang City, so that the Magelang City Vocational Training Center can identify entrepreneurial interests, develop open innovation and skill training for MSME business actors. This research is an empirical interpretative design with a quantitative approach. While testing the hypothesis, researchers used multiple linear regression analysis, t-test, and test the coefficient of determination. From the results of this study, it is known that interest in entrepreneurship, training skills, and open innovation influence the sustainability of MSMEs. This result of the analysis shows that to increase the sustainability of MSMEs, interest in entrepreneurship, skills training, and open innovation also needs to be increased